2016
DOI: 10.3389/fmicb.2016.00593
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota of Broiler Chickens As Affected by Litter Management Regimens

Abstract: Poultry litter is a mixture of bedding materials and enteric bacteria excreted by chickens, and it is typically reused for multiple growth cycles in commercial broiler production. Thus, bacteria can be transmitted from one growth cycle to the next via litter. However, it remains poorly understood how litter reuse affects development and composition of chicken gut microbiota. In this study, the effect of litter reuse on the microbiota in litter and in chicken gut was investigated using 2 litter management regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
146
3
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(174 citation statements)
references
References 65 publications
11
146
3
14
Order By: Relevance
“…As discussed earlier [1, 34, 48], differences in host (genetics, breeds, anatomical features of the gut, physiology, etc. ), litter management, and diets might be attributable to the distinct GI bacteriomes in the chicken and turkey.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed earlier [1, 34, 48], differences in host (genetics, breeds, anatomical features of the gut, physiology, etc. ), litter management, and diets might be attributable to the distinct GI bacteriomes in the chicken and turkey.…”
Section: Resultsmentioning
confidence: 99%
“…That study revealed that the fresh litter and reused litter affected the GI microflora of broiler chickens (Wang et al, 2016). While that study pioneered a new area of research, the feeding condition, not just the litter but housing system could affect the GI microflora of chickens.…”
Section: Introductionmentioning
confidence: 99%
“…; Wang et al . ). However, the old litter provides a suitable environment for different kinds of living organisms, including pathogenic microbes such as coccidia (Lu et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the poultry industry, it is common to reuse old litter for more than one cycle (Coufal et al 2006;Wang et al 2016). However, the old litter provides a suitable environment for different kinds of living organisms, including pathogenic microbes such as coccidia (Lu et al 2003).…”
Section: Introductionmentioning
confidence: 99%